Peran Guru Pendidikan Agama Kristen Dalam Mengatasi Krisis Kerohanian Anak Sekolah Minggu - Salome Salome; Lisna Novalia (Publisher STPKat, 2023)
The spiritual crisis among Sunday school children has become a serious concern in the context of Christian religious education. This article examines the important role played by Christian religious education teachers in overcoming this crisis. In a modern context full of challenges, children often experience spiritual isolation, loss of religious values, and difficulty implementing Christian principles in everyday life. Christian religious education teachers have a responsibility to provide guidance and inspiration to these children. This article examines strategies and methods Christian religious education teachers can use to help Sunday school children overcome spiritual crises. Some of the strategies described include the use of interesting Bible stories, interactive and creative teaching, building empathetic relationships with students, and encouraging reflection and application of Christian values in everyday life. Christian religious education teachers must also be able to tactfully face children's questions and doubts, and develop a deep understanding of children's spiritual and developmental needs. Through their role, Christian religious education teachers can be role models and sources of inspiration for Sunday school children in strengthening their faith and dealing with spiritual crises. In carrying out their duties, teachers must have a strong commitment to the mission of Christian religious education and pay attention to the social and cultural changes that affect children's lives. This article aims to inform and motivate Christian religious education teachers in carrying out their roles more effectively and relevantly amidst the spiritual crisis of Sunday school children. Through collaborative efforts between the church, parents and the Christian community, it is hoped that Sunday school children can obtain a solid foundation of faith and be able to overcome the spiritual challenges they face in their lives.